Assessment of farmer willingness to pay for quality planting materials of biofortified and non-biofortified varieties of sweetpotato. - Mwiti, F.K.; Okello, J.J.; Munei, K.; Low, Jan W. (2016)
The current fight against Vitamin A deficiency has focused on promoting biofortified staples that are rich in beta carotene, such as Orange Fleshed Sweetpotato (OFSP). These efforts usually entail providing quality planting materials to vulnerable households accompanied by sensitization about the benefits of OFSP. Most such interventions heavily subsidize the planting materials, with subsidies ranging from 50-100%. The subsidies are often premised on the hope that farmers will eventually absorb the full cost of the planting materials once they experience the benefits of consuming OFSP. This study uses data from 481 farmers drawn from different regions that benefited from a sweetpotato project, and the ANOVA and descriptive statistics, to examine farmers’ willingness to pay (WTP) for OFSP planting materials. It specifically compares the WTP for quality planting materials of OFSP and non-OFSP varieties and assesses differences in WTP by region and agroecology. It finds a higher WTP for clean planting materials of a non-OFSP variety than for all OFSP varieties studied. It also finds that WTP differs by region and agroecology. The study concludes that there is higher demand for quality planting materials of some of the non-OFSP varieties of sweetpotato than for OFSP varieties, and that WTP for differs by intervention area. These findings imply that farmers’ demand for clean planting materials of non-OFSP varieties is higher than for the OFSP varieties. They suggest the need for sweetpotato breeding to continue considering some of the attributes that make local varieties popular, e.g., taste and dry matter content, in their breeding programs.